LINGUISTIC FEATURES OF LOVERS’ SPEECH IN CONTEMPORARY GERMAN-LANGUAGE FICTION - DZIUBENKO, Viktoriia; ONISHCHENKO, Nataliia (Accents and Paradoxes of Modern Philology, 2026)
The discourse of lovers in contemporary German-language literary texts is a complex linguistic phenomenon that integrates cognitive, pragmatic, stylistic, and cultural aspects. This study examines semantic, syntactic, and stylistic features of romantic communication based on three modern German novels: Tschick by Wolfgang Herrndorf (2010), Allegro Pastell by Leif Randt (2020), and Das Leben fing im Sommer an by Christoph Kramer (2025). The aim of the research is to identify linguistic features that shape lovers’ discourse and to analyze their pragmatic functions and expressive potential. The objectives include a theoretical overview of discourse studies, classification of romantic discourse within personal dialogic interaction, conceptualization of love in literary context, and analysis of lexical, syntactic, and stylistic patterns in lovers’ speech. The theoretical framework combines cognitive-discursive, sociolinguistic, and pragmatic approaches. The methodology includes content analysis, lexical-semantic, syntactic and stylistic analysis, and comparative textual study. The study identifies typical linguistic devices of romantic discourse: emotionally charged vocabulary, idioms, metaphors, syntactic fragmentation (ellipsis, repetition, exclamations), stylistic techniques (irony, language play, affectionate diminutives). These elements model intimacy, spontaneity, and emotional depth in character interaction. The research also emphasizes the interplay between verbal and nonverbal communication and the cultural specificity of linguistic expressions of love. The results may be useful for further studies in discourse analysis, literary linguistics, and translation studies.